Respuesta :

Answer: t = (5x² - 6x - 1)/(3x² - 5x²)

Step-by-step explanation:

               3tx - 5x = (t + 2)(t - 3) - t² - [tex]\frac{1}{x}[/tex]

               3tx - 5x = t² - t - 6 - t² - [tex]\frac{1}{x}[/tex]

               3tx - 5x = - t - 6 - [tex]\frac{1}{x}[/tex]

            3tx² - 5x² = -tx - 6x - 1

            +tx + 5x²    +tx + 5x²    

             3tx² + tx =  5x² - 6x - 1

        t(3x² - 5x²)  = 5x² - 6x - 1

      ÷ (3x² - 5x²)  ÷ (3x² - 5x²)

                       t = (5x² - 6x - 1)/(3x² - 5x²)